Preparation of Super Absorbent and Highly Active Fish Collagen Sponge and its Hemostatic Effect in vivo and in vitro - Wang, Lei; Li, Wenjun; Qu, Yan; Wang, Kai; Lv, Kangning; He, Xiaoli; Qin, Song (Frontiers in Bioengineering and Biotechnology, 2022)
Effective control of acute wound hemorrhage during battlefields, car accidents, natural disasters and so forth can highly increment patient survival rates. Nevertheless, current commercially available hemostatic materials have various defects and limitations. This study utilizes tilapia to extract macromolecular type I collagen to prepare a new hemostatic sponge for acute wound bleeding control. The fish collagen that extracted has high purity, uniform molecular size and high hydroxyproline content. The peptide chain structure and natural high-level structure are intactly preserved. Infrared absorption spectrum showcases that it preserves all the characteristic absorption bands of type I collagen. The hemostatic sponge that prepared has a uniform honeycomb-shaped porous structure, which has high water absorption capacity. The biological safety test illustrates that the sponge cell has good compatibility, which will not cause any inflammatory reaction and other immune rejection reactions in the body. The sponge cell could be degraded gradually and completely, which has good biocompatibility and degradation performance. In vitro tests have demonstrated that certain groups or structures in fish collagen molecules can bind to specific sites on the surface of blood cells and platelets, which can quickly activate platelets and coagulation system to obtain excellent coagulation ability. In vivo experiments further find that the fish collagen sponge has fast coagulation speed and low bleeding during the hemostasis process of rabbit ear arteries and rat liver wounds, which has excellent coagulation performance.